Digital Marketing Strategy for Local Business Imanee Clothing Line - Mitha Prissca; Nuri Wulandari (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Local fashion brands in Indonesia are now starting to appear in the market and are growing rapidly. One fashion brand, Imanee, offers quality dresses with casual and elegant designs. Imanee stands as an offline store in the city of Bangka. However, the phenomenon that occurs is that sales are less significant. Therefore, this study aims to produce a digital marketing strategy so that the Imanee fashion brand can reach a wider range of consumers, increase awareness, sales and retention. To achieve this goal, the research method was carried out using Porter's Five Forces analysis. Furthermore, using qualitative data on six respondents through in-depth interviews with the framework of the Customer Journey and Marketing 4P (Product, Promotion, Price, Place). The results of the study indicate that Imanee's business conditions are in intense competition. Imanee products have met buyer satisfaction with the hope that the product can add designs to follow trends and issue large sizes. The price of the product is in accordance with the quality offered. Based on in-depth interviews, it can be said that the top platforms that can be used for a base in the digital market are shopee, instagram, and tiktok. Through this research, the resulting marketing strategy is in the form of a long-term implementation plan with a one-year target. which are categorized into high, medium and low priority based on the criteria of low cost and high impact. The implementation plan includes product development and social media outreach. With this strategy, it is hoped that Imanee will be able to compete in the red ocean market and increase its competitive advantage to win the market.